2018
DOI: 10.3329/agric.v15i2.35463
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Characteristics and Yield Performance of Mungbean (<i>Vigna radiata</i> L.) Varieties under Different Levels of Shading

Abstract: An experiment was carried out to evaluate the leaf characteristics and yield performances of mungbean (Vigna radiata L.) under different light levels at the Crop Physiology and Ecology Research Field of Hajee Mohammad Danesh Science and Technology University, Dinajpur during March to June 2016. The experiment was laid out in a split plot design with three replications. Three light levels (L 100 -100 % light intensity, L 75 -75 % light intensity and L 50 -50% light intensity) were assigned in the main plots and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The varieties that have grown taller (DBGV 5, CO 6 and Sumanj ana) were found adapted to partially shaded conditions by stem elongation for radiation energy capture and use in photosynthesis. Similar results of increment in plant height with shade was observed by Lakshmamma and Rao (1996) in blackgram and Hossain et al (2017) and Nair (2020) in green gram under partially shaded coconut garden. Keuskamp et al (2010) reported that as shading stimulates the synthesis of auxin and gibberellins, plant show increased height and etiolated leaves, since these hormones promotes cell division, cell elongation, apical dominance and inter nodal elongation.…”
Section: Growth Characterssupporting
confidence: 85%
“…The varieties that have grown taller (DBGV 5, CO 6 and Sumanj ana) were found adapted to partially shaded conditions by stem elongation for radiation energy capture and use in photosynthesis. Similar results of increment in plant height with shade was observed by Lakshmamma and Rao (1996) in blackgram and Hossain et al (2017) and Nair (2020) in green gram under partially shaded coconut garden. Keuskamp et al (2010) reported that as shading stimulates the synthesis of auxin and gibberellins, plant show increased height and etiolated leaves, since these hormones promotes cell division, cell elongation, apical dominance and inter nodal elongation.…”
Section: Growth Characterssupporting
confidence: 85%
“…Also, Tripathi et al (2020) reported similar h 2 for DFF (62.5%), DFPF (83.6%) and DHPF (95%). Leaf area ranged for leaflets from 99.42 cm 2 (33.21/leaf) to 221.30 cm 2 (73.76/leaf), Similarly, Hossain et al (2017) observed that the leaf area range concerning light in different (30, 40, and 50 days) showed range from minimum 96.29 cm 2 /leaflet to maximum 461.96 cm 2 /leaflet. Whereas Kaur & Kumar (2020) reported leaf area in mungbean ranging from 27 cm 2 /leaf to 30 cm 2 /leaf.…”
Section: Discussionmentioning
confidence: 68%
“…The shading effect of maize and chili plants in the maize + mungbean + chili treatment (the position of the row of mungbean crops was between the rows of maize and chili plants), was likely to be the low productivity of mungbean crops in the strip intercropping treatment. It was previously reported that some varieties of mungbean crops are relatively sensitive to shade, so it can reduce crop yields (Hossain et al, 2017). The selection of mungbean varieties that are relatively tolerant to shade is important in diversifying crops through intercropping.…”
Section: Resultsmentioning
confidence: 99%